On-farm nursery technique for acclimatization of Tissue-Cultured Banana (Musa acuminata cv. Berangan) seedlings - Wong Kah Fei (2018)
Bananas are well-known fruit in the world, where the need and demand are increasing all year-round. However, the production keeps reducing as compared to the previous years. Insufficient supply of quality planting materials is the main issue apart from the disease problem. Tissue-cultured banana seedlings is widely used as planting materials, but it is not preferred by small-scale farmers due to extra care that needs to be taken during the nursery stage. High mortality rate in both nursery and field planting stage has been observed due to improper handling by untrained farmers. Research has been conducted to improvise the nursery technique in order to accommodate farmers in handling tissue-cultured seedlings. Based on the results, the developed technique used has increased the seedlings’ survival rate (90%) as compared to the conventional technique (46.7%) in on-farm nursery stage. While comparing both techniques used in conventional netted house, the developed technique still resulted in higher seedlings’ survival rate (96.7%) as compared to the conventional technique (75%). The developed technique used in on-farm nursery required shorter hardening period (30-32 days) than both the developed technique (44-46 days) and conventional technique (60-70 days) used in netted house in achieving equivalent seedlings’ physical quality. In field planting study, equivalent physical quality seedlings hardened with developed technique practised in both farm nursery and conventional netted house were compared with the seedlings hardened with conventional technique practised in conventional netted house. The results show that seedlings hardened with developed technique practised in both farm nursery and netted house marked 100% and 90% of survival rate respectively, whereas seedlings hardened with conventional technique in netted house only marked 60% of survival rate. Besides, seedlings hardened with developed technique shows shorter time in overcoming transplanting shocks and growing rapidly as compared to others. In short, the developed hardening technique enables to provide tissue-cultured seedlings with higher survival rate and physical quality in both nursery and field planting stage within shorter nursery period. High post-planting survival and quality grow properties could encourage farmers to use tissue-cultured seedlings as planting materials. With the success in providing enough high quality and quantity of planting materials, bananas’ productions are secured and will give benefits to all banana-based industries.